The synergistic effect of Ï‰3 and Vit D3 on glycemia and TNF-Î± in islet transplantation - Gurol, A O; Okten-Kursun, A; Kasapoglu, P; Suzergoz, F; Kucuksezer, U C; Cevik, A; Tutuncu, Y; Yentur, S P; Gurol, S D; Kucuk, M; Yilmaz, M T (Cellular and Molecular Biology, 2016)
The current treatment of type 1 diabetes consists of insulin administration. Transplantation of islets of Langerhans is considered very favorable because the full effect of insulin treatment cannot be obtained in severe cases. Although agents such as omega-3 (Ï‰3) and vitamin D3 (Vit D3) are known to contribute to the success of islet allo-transplantation (ITX), in this study we aimed to experimentally determine their effects on glycemia and TNF-Î± production. Wistar albino rats, which were used as recipients, were given Ï‰3, Vit D3, and islets by gavage, and intraperitoneal- and intraportal injections, respectively. Daclizumab (DAC) was used for immunosuppression. Glycemia levels decreased in rats treated with Ï‰3 and vit D3. TNF-Î± increased in all groups due to application of STZ. After ITX (day +1), the weakest increase was observed in the Ï‰3 + Vit D3 group. In the ITX+DAC group, compared with that of ITX only, DAC was shown to decrease levels of TNF- Î± following ITX, only in control group, however, similar levels of TNF-Î± were observed in other groups. The values in the treated groups were already lower than those of the controls in the ITX group and also remained almost equal in the ITX+DAC group. We suggest that the use of Ï‰3 and Vit D3 together will improve the pro-inflammatory aspect encountered during and after ITXs, and contribute to the reduction of the dose of immunosuppressants in these procedures.